Perfil epidemiológico da hanseníase no estado do Paraná em período de eliminação - Silva Sobrinho, Reinaldo Antonio da (2007)
Hansen's Disease, a national endemic infectious disease, although having presented some degree of decrease in it's prevalence in the last years, is yet considered a public health problem in most of Brazilian states. This study aims at analysing Hansen's Disease detection and prevalence rates in between the years of 2000 and 2005 and sociodemographic, clinic and observation characteristics of subjects who were enrolled on the Programa de Controle da Hanseníase (Hansen's Disease Control Program) of Parana state in 2005. The source of information was the Sistema de Informação de Agravos de Notificação - SINAN, provided by the Parana Health State Office and also the TABNET MS/DATASUS software available on the Health State Department website. The detection and prevalence rates of Hansen's Disease during the period ranged from 2000 to 2005, as well as the variables on notification records of the disease for 2005 were analysed using the TABWIN/DATASUS software. Absolute and relative frequencies were obtained in percentuals and rates. According to health regional offices in Parana state, it was observed that Hansen's Disease detection was wether high or very high. As for prevalence, eight regional health offices reached the elimination objectives according to parameters established by the Health State Department. The detection and prevalence rates of Hansen's disease in Parana remained unaltered during this study. The analysis of sociodemographic variables for 2005 revealed that the disease affected male subjects the most (55,1%), whose age ranged from 20 to 49 years old (50,8%), white (76,4%), with low degree of tuition (82,5%) and urban residents (81,6%). The virchowian and multibacillary clinic forms were the most frequent, with 32,7% and 64,7% rates, respectively. The detection way mostly verified for Hansen's was the conduction of subjects, 53,8%. From the number of indetermined clinic forms, 6,8% were treated as multibacillary and 19,3% of the cases notified as having no lesions or unique skin lesions received multibacillary treatment. The number of people who returned to treatment after reincidence was about 6,9%. As a conclusion, the state of Parana will possibly take some years to reach the objective of Hansen's Disease elimination because of the existence of late detection areas, characterized by the high percentage of cases in the disease's serious forms, high prevalence rates in some regional health offices and the high number of detected cases. It is recommended that in order to eliminate Hansen's Disease effectively, diagnosis efforts are increased, the early detection, prevention and physical incapabilities treatment are made, symptoms and signs made public and continued education of health care workers carried on as a way to implement and solidify the disease's control activities on basic attention are observed.